2008
DOI: 10.1016/j.pbb.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of (+)-methamphetamine in the pigeon following an intramuscular dose

Abstract: Pigeons are used frequently as subjects in behavioral pharmacology research. An advantage of the pigeon is an exceedingly vascular breast muscle, which is easily accessible for injections. The purpose of these studies was to provide a profile of the pharmacokinetics of (+)-methamphetamine (METH) and (+)-amphetamine (AMP), a pharmacologically active metabolite, in pigeons (n = 6) after intramuscular (IM) and intravenous (IV) dosing (0.8 mg/kg). LC-MS/MS analysis was used to determine serum concentrations of MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Although no study to our knowledge has examined the effect that different routes of administration may have on meth metabolism, recent work (Hendrickson et al, 2008) with pigeons suggests that administration of meth either intramuscularly or intravenously does not affect metabolism. Nevertheless, route of administration should be examined in future investigations, given that it results in differences in bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Although no study to our knowledge has examined the effect that different routes of administration may have on meth metabolism, recent work (Hendrickson et al, 2008) with pigeons suggests that administration of meth either intramuscularly or intravenously does not affect metabolism. Nevertheless, route of administration should be examined in future investigations, given that it results in differences in bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…METH pharmacokinetics have been studied under various conditions by several groups of investigators ( Berquist et al, 2020 ; Hendrickson et al, 2008 ; Milesi-Halle et al, 2015 ; Rambousek et al, 2014 ). Milesi-Halle et al (2005) reported on sex- and dose-differences in the pharmacokinetics of METH and amphetamine (AMPH) in male and female Sprague-Dawley rats after administering 1.0 and 3.0 mg/kg METH doses.…”
Section: Animal Models Of Methamphetamine Use Disordermentioning
confidence: 99%
“…absorption was three times higher than i.m. In this regard, some studies support that injection of METH in ranges of 3.6–10 mg/Kg are considered lethal in animals (Hendrickson et al, 2008 ). Similarly, a recent study showed an 8-fold higher catalytic activity of METH in rhesus macaques compared to humans due to enzymatic differences (Earla et al, 2014 ).…”
Section: Pharmacological Meth Levels In Animalsmentioning
confidence: 99%